Non-neoplastic astrocytes: key players for brain tumor progression - Catalano, Myriam; Limatola, Cristina; Trettel, Flavia (Frontiers in Cellular Neuroscience, 2024)
Astrocytes are highly plastic cells whose activity is essential to maintain the cerebral homeostasis, regulating synaptogenesis and synaptic transmission, vascular and metabolic functions, ions, neuroand gliotransmitters concentrations. In pathological conditions, astrocytes may undergo transient or long-lasting molecular and functional changes that contribute to disease resolution or exacerbation. In recent years, many studies demonstrated that non-neoplastic astrocytes are key cells of the tumor microenvironment that contribute to the pathogenesis of glioblastoma, the most common primary malignant brain tumor and of secondary metastatic brain tumors. This Mini Review covers the recent development of research on non-neoplastic astrocytes as tumor-modulators. Their double-edged capability to promote cancer progression or to represent potential tools to counteract brain tumors will be discussed.